The Role Of Foreign Direct Investment In The Organization And Development Of An Innovation Cluster - Khoshimov Sabir Murtazaevich; Ganiev Shahiriddin Vohidovich (Global Scientific Publishing, 2023)
The article examines the role and importance of creating innovative clusters in the socio-economic development of the country, the role and importance of foreign direct investment in the development of clusters, and discusses conclusions and recommendations based on international experience.
Keywords: foreign direct investment; innovation; cluster; globalization